2022
DOI: 10.1055/a-1718-6283
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Thyroid Hormones with Coronary Atherosclerotic Severity in Euthyroid Patients

Abstract: The aim of the work was to explore the correlation between thyroid hormones and coronary atherosclerotic severity. This cross-sectional study included 340 euthyroid patients who underwent diagnostic coronary artery angiography (CAG). Gensini Score (GS) was applied to assess the severity of coronary atherosclerosis. Thyroid hormones and routine biochemical parameters were measured. The associations between thyroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Interestingly, our study also found that when used as a reference in the Q1 group, peripheral thyroid hormone sensitivity index FT3/FT4 was negatively associated with carotid plaque in the Q4 group, and the sensitivity was the strongest in the Q4 group. As many studies confirmed the positive effects of elevated FT3/FT4 on cardiovascular risk and arterial stiffness markers (39)(40)(41). However, studies have reported conflicting views.…”
Section: Discussionmentioning
confidence: 83%
“…Interestingly, our study also found that when used as a reference in the Q1 group, peripheral thyroid hormone sensitivity index FT3/FT4 was negatively associated with carotid plaque in the Q4 group, and the sensitivity was the strongest in the Q4 group. As many studies confirmed the positive effects of elevated FT3/FT4 on cardiovascular risk and arterial stiffness markers (39)(40)(41). However, studies have reported conflicting views.…”
Section: Discussionmentioning
confidence: 83%
“…Its biologic function is considered to be related to the inhibition of bone matrix mineralization [35,36]. In addition, multiple cross-sectional studies have found that FT3/FT4, TSHI, and TT4RI are significantly correlated with chronic kidney disease (CKD), non-alcoholic fatty liver disease (NAFLD), and coronary artery disease (CAD) [37][38][39]. As described in this article, we found that FT3/FT4 levels decreased with increasing risk of OA, whereas TSHI and TT4RI levels increased with increasing OA prevalence in the subjects.…”
Section: Discussionmentioning
confidence: 99%
“…19 These new comprehensive indicators can systematically reflect the regulation of TH homeostasis. They may be less biased than single indicators with a better explanation for the various associations between TH changes and the risk of DR. TSHI and TT4RI are significantly linked to the prevalence of coronary heart disease (CAD), 27 NAFLD, 28 and chronic kidney disease. 29 A strong link was discovered between TFQI and obesity, metabolic syndrome, and diabetes-related mortality.…”
Section: Discussionmentioning
confidence: 99%